Pendidikan Seks Bagi Remaja (Perspektif Abdullah Nashih Ulwan dan Ali Akbar) - Siti Rohmaniah (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
In Islam sex education gets serious attention to be taught to teenagers. One of them, according to Muslim figures Abdullah Nashih Ulwan and Ali Akbar. The results of this study are: 1) Sex education according to Abdullah Nashih Ulwan's view is an effort to teach, raise awareness and explain sexual problems to adolescents, since he is familiar with problems related to sexual and marital instincts through the methods of awareness, warning and binding, 2) Sex Education according to Ali Akbar that Islam regulates sexuality starting from the genitals, clothing, vision and sex, lust itself, 3) a.The similarities between Abdullah Nashih Ulwan and Ali Akbar's thoughts on sex education are that the two figures in providing sex education are based on religious education. In discussing the concept of sex education, the two characters use a psychological approach. b. The difference in thinking about sex education according to Abdullah Nashih Ulwan and Ali Akbar is that Abdullah Nashih Ulwan in his concept is more inclined to the process, while Ali Akbar is inclined to the material.